Batik Motif of Mathematical Modeling of Dengue Fever Transmission with the Social Awareness Factor - Mubarok, Faqih Ainul; Abizart, Muhammad; Syafaat, Muhammad Ali; Sugiyanto, Sugiyanto (Proceeding International Conference on Religion, Science and Education, 2026)
Dengue Hemorrhagic Fever (DHF) remains one of the major public health problems in tropical regions, including Indonesia. The transmission rate of this disease is strongly influenced by various factors, particularly the level of social awareness within the community toward prevention and control efforts. This study formulates a mathematical model of DHF transmission by incorporating the social awareness factor as an additional compartment. The analysis involves determining the equilibrium points and the basic reproduction number (R0), as well as testing the stability of the system using the Routh–Hurwitz criteria. The results show two types of equilibrium points, namely the disease-free point (T1) and the endemic point (T2). The point T1 is locally stable when R0<1 and becomes unstable when R0>1, while point T2 is locally stable if R0>1. Sensitivity analysis indicates that the social awareness parameter has a significant influence on the value of R0. Furthermore, numerical simulations demonstrate that an increase in social awareness can effectively suppress disease transmission and lead the system toward a disease-free condition. These findings highlight the importance of enhancing public awareness as a key component of sustainable dengue control strategies.